Fishing and Fishermen in Jerez de la Frontera at the End of the Fifteenth century: the Presence of the Fleet of San Vicente de la Barquera (Edad Media. Revista de Historia, 2019)
The municipality district of Jerez de la Frontera lost its coastal belt after the foundation of Puerto Real in 1483. The town, since then, was unable to provide the right environment for the development of its own fishing fleet. Although it still possessed important fluvial fishing grounds, especially those on the Guadalete river course, both the local landowners and the council institution restricted the access to such resources. Public fishing was limited and only those catches carried out in riverside areas under yearly tax control were allowed. Given the subsequent low-volume and weakness of Jerez fisheries and the need to supply the fish market of one of the most densely populated towns in Andalucía, the signing of agreements between the local council and the Cantabrian fishermen from San Vicente de la Barquera comes as no surprise. This would account as well for the settlement of such San Vicente de la Barquera dwellers within Jerez municipal borders by the end of the fifteenth century.
Keywords: Fishing; Fishermen; Jerez de la Frontera; San Vicente de la Barquera; Siglo XV